Distance education during the COVID-19 pandemic: Development features - Nikolaeva, Evgeniya Mikhailovna; Kotenkova, Svetlana Nikolaevna; Eflova, Maria Yurievna; Kotliar, Polina Sergeevna (Linguistics and Culture Review, 2021)
An existential problem for modern society is the stability problem when the ambiguity of extended forecasts becomes characteristic even for the foreseeable future. Consideration of this problem from the perspective of the digital space is especially important for two reasons. First, the bulk of modern communication processes takes place in the network space. Second, the processes of searching, consuming, exchanging information and acquiring new knowledge are directly or indirectly connected today with digital resources. This article deals with the analysis of the specifity of the implementation of distance learning in the context of the Covid-19 pandemic. The empirical study base is a group interview with students of Kazan Federal University which has highlighted students’ attitudes over online education in the face of a pandemic. The analysis of the respondents’ viewpoints reveals several common stances towards understanding their individual educational strategy, and the results of the study enable to determine the specific features of the implementation of training for students of Kazan Federal University, to show the features of the influence of distance learning on the choice of educational technologies. The differences between the students’ attitudes over the development of remote education are revealed.